2018
DOI: 10.1093/jn/nxy104
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Receptor or TGF-β Neutralization Abrogates the Protective Effect of a Specific Nondigestible Oligosaccharide Mixture in Cow-Milk-Allergic Mice

Abstract: BackgroundDietary nondigestible, short-chain galacto-, long-chain fructo-, and pectin-derived acidic oligosaccharides (GFAs) lower the effector response in cow-milk-allergic (CMA) mice; and forkhead box P3 (Foxp3)–positive regulatory T cells (Tregs) were shown to contribute to this.ObjectiveThe aim of this study was to assess the contribution of interleukin 10 (IL-10) and transforming growth factor β (TGF-β) to the protective effect of the GFA diet in CMA mice.MethodsFemale C3H/HeOuJ mice, 3–4 wk old, were ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The different POS can include galacturonic acid (GalA), rhamnose (Rha), arabinose (Ara), and galactose (Gal) [52]. GFAs, consisting of pAOS, have shown to lower immune responses in cow-milk-allergic (CMA) mice, to enhance regulatory T cell (T reg ) frequencies, and to induce mucosal IL-10 and TGF-β transcription while suppressing the allergic effector response [53]. Both animal studies and human clinical trials showed that dietary intervention with these dietary oligosaccharides early in life could lead to the prevention of atopic dermatitis, food allergy, and allergic asthma [10,37,54,55].…”
Section: Pectin Structurementioning
confidence: 99%
“…The different POS can include galacturonic acid (GalA), rhamnose (Rha), arabinose (Ara), and galactose (Gal) [52]. GFAs, consisting of pAOS, have shown to lower immune responses in cow-milk-allergic (CMA) mice, to enhance regulatory T cell (T reg ) frequencies, and to induce mucosal IL-10 and TGF-β transcription while suppressing the allergic effector response [53]. Both animal studies and human clinical trials showed that dietary intervention with these dietary oligosaccharides early in life could lead to the prevention of atopic dermatitis, food allergy, and allergic asthma [10,37,54,55].…”
Section: Pectin Structurementioning
confidence: 99%
“…In a murine model for hen's egg allergy, 2'FL or 6'SL were found to reduce allergy symptoms in association with the induction of IL-10 + T reg cells (39). Prebiotic mixtures, such as scGOS and lcFOS, have been studied more extensively for immunomodulatory effects in vivo, showing promising results with regards to preventing allergic diseases, such allergic asthma and food allergy and these effects also link to the induction of T reg responses (134)(135)(136)(137). This implies a need for additional in vivo studies to gain insight in the properties of (single) HMOS to modulate gut maturation and the development of the mucosal immune system.…”
Section: Hmos Strengthening the Intestinal Epithelial Integritymentioning
confidence: 99%
“…Cow milk or the recombinant growth factor was shown to increase plasma TGF-β concentrations (Ando et al, 2007;Ozawa et al, 2009). Additionally, the allergy-protective effect of dietary acidic oligosaccharides is mediated by TGF-β in mice with cow milk allergy (Kerperien et al, 2018). Cow milk had significant beneficial effects on skin wound healing in a preclinical model (Hemmati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%